Anodic mesoporous TiO(2) layer on Ti for enhanced formation of biomimetic hydroxyapatite - Dey, Tuli; Roy, Poulumi; Fabry, Ben; Schmuki, Patrik (Acta Biomaterialia, 2010)
Ti surfaces can be very efficiently coated by a robust ( extgreekmm thick) mesoporous titania layer (MTL). These coatings are produced by anodization of Ti at elevated temperature in a glycerol/K2HPO4 electrolyte, followed by an appropriate etching process. In the present work we examine these layers with regard to their ability to form hydroxyapatite. Immersion tests in two types of simulated body fluids (Kokubo SBF and Bohner and Lemaitre SBF) combined with scanning electron microscopy, X-ray diffraction and X-ray photoelectron spectroscopy investigations show that these MTL layers lead to a significant enhancement of HAp formation and anchoring in the structure compared with non-coated or even nanotubular Ti surface coatings (these were recently reported to be the most efficient in terms of HAp formation).